How many animals are used for SARS‐CoV‐2 research?: An overview on animal experimentation in pre‐clinical and basic research. (7th September 2021) - Schwedhelm, Philipp; Kusnick, Johanna; Heinl, Céline; Schönfelder, Gilbert; Bert, Bettina
Abstract : Non‐technical summaries of research projects allow tracking the numbers and purpose of animal experiments related to SARS‐CoV2 research so as to provide greater transparency on animal use.